Development of a prototype automatic sauce dispenser / Asif Muhaimin Mohd Saiful Nizam and Norjasween Abdul Malik - Mohd Saiful Nizam, Asif Muhaimin; Abdul Malik, Norjasween (School of Mechanical Engineering, 2023)
Currently, manual sauce dispensers are commonly used tools in many restaurants for dispensing condiments such as ketchup, mustard, and mayonnaise onto dishes. However, these manual dispensers can be messy and may result in uneven distribution of the sauce. An engineering solution to address these challenges is the Automatic Sauce Dispenser. This project aims to design, analyze, and fabricate an Automatic Sauce Dispenser that can automatically dispense sauce upon detecting the cup. The Automatic Sauce Dispenser is a machine that enhances the efficiency and speed of sauce dispensing, reducing the time required for users. It incorporates sensors and LED lights to indicate when the sauce needs to be refilled. By utilizing sensors, the dispenser automatically detects the cup's presence and dispenses the sauce accordingly. In conclusion, the Automatic Sauce Dispenser has been successfully designed, fabricated, and is fully functional. This product offers benefits to fast-food restaurants by reducing time consumption and improving hygiene in the surrounding area. The Automatic Sauce Dispenser provides a convenient and precise way to dispense sauce, potentially reducing waste and making meal preparation and cleanup easier.